Pengaruh Aplikasi Beberapa Jenis dan Dosis Pupuk Organik Terhadap Kualitas Pascapanen Bunga Matahari (Helianthus annuus L.) - Krisnamurti, Gusti Putu Maesa; Sukewijaya, I Made; Astawa, I Nyoman Gede (Nandur; Vol 3 No 4 (2023), 2023)
Sunflower ( Helianthus annuus L.) is a type of ornamental plant that has considerable potential to be used as a commercial cut flower. For this reason, it is necessary to add nutrients in the form of organic and inorganic fertilizers. The application of organic fertilizers in plant cultivation can improve plant growth media and as a source of macro and micro nutrients. The use of organic fertilizers is also important for ornamental plants in affecting the quality of flowers and flower vase life . This study aims to determine the effect of the type and dose of fertilizer on the growth of sunflower (Helianthus annuus L.) and to determine the effect of the type and dose of fertilizer on the postharvest quality of sunflower (Helianthus annuus L.). The design of this study used a factorial randomized block design (RBD) with 2 factors. The first factor was the type of organic fertilizer consisting of 3 levels and the second factor was the dose given which consisted of 4 levels repeated three times. The selected manure has been composted for approximately 28 days. The results showed that chicken manure had a better effect than cow manure and goat manure. As for the dose treatment, it was found that the dose of P3 manure (dose of 211.95 gr) had the best effect on plant height and vase life variables of sunflowers.